Systematic review and meta‐analysis of effectiveness of treatment options against SARS‐CoV‐2 infection. Issue 2 (22nd July 2020) - Thoguluva Chandrasekar, Viveksandeep; Venkatesalu, Bhanuprasad; Patel, Harsh K.; Spadaccini, Marco; Manteuffel, Jacob; Ramesh, Mayur
Abstract: Treatment options for severe acute respiratory syndrome‐related coronavirus‐2 (SARS‐CoV‐2) are limited with no clarity on efficacy and safety profiles. We performed a systematic review and meta‐analysis of studies on patients ≥18 years reporting data on therapeutic interventions in SARS‐CoV‐2. Primary outcome was all‐cause mortality and secondary outcomes were rates of mechanical ventilation, viral clearance, adverse events, discharge, and progression to severe disease. Pooled rates and odds ratios (OR) were calculated. Twenty‐nine studies with 5207 patients were included. Pooled all‐cause mortality in intervention arm was 12.8% (95% confidence interval [CI]: 8.1%‐17.4%). Mortality was significantly higher for studies using hydroxychloroquine (HCQ) for intervention (OR: 1.36; 95% CI: 0.97‐1.89). Adverse events were also higher in HCQ subgroup (OR: 3.88; 95% CI: 1.60‐9.45). There was no difference in other secondary outcomes. There is a need for well‐designed randomized clinical trials for further investigation of every therapeutic intervention for further insight into different therapeutic options. Highlights: Our meta‐analysis of 5207 patients showed that the use of hydroxychloroquine was associated with increased mortality and adverse event rates in Severe acute respiratory syndrome‐related coronavirus‐2 infection and other therapeutic interventions did not show any difference in outcomes.